The Effect of Leadership Style and Work Motivation on Employee Productivity in the Batam City Government with Work Environment as an Intermediary Variable - Aziz, Syahibul; Ratnasari, Sri Langgeng; Nasrul, Herni Widiyah (JURNAL TRIAS POLITIKA, 2025)
This study analyzes the influence of leadership style and work motivation on employee productivity in the Batam City Government (Pemko Batam), considering the work environment as an intermediary variable. The method used is a mixed approach between qualitative and quantitative methods. For the qualitative approach, in-depth interviews, field observations, and document studies related to the research object were conducted. Meanwhile, for the quantitative approach, a survey was conducted on 250 employees at Pemko Batam, with data collected through questionnaires distributed using purposive sampling. The results of the study show that both qualitative and quantitative approaches have the same correlation results: leadership style significantly affects employee productivity, work motivation has a positive relationship with employee productivity, and the work environment is proven to act as an intermediary variable that affects the relationship between leadership style and work motivation with employee productivity in the Batam City Government.